Enhancing the effectiveness of CMIM and AMRO: Selected immediate challenges and tasks - Reza Siregar; Akkharaphol Chabchitrchaidol (Asian Development Bank Institute (ADBI), 2013)
The Chiang Mai Initiative Multilateralisation (CMIM) and the ASEAN+3 Macroeconomic Research Office (AMRO), established in March 2010 and May 2011, respectively, have made substantial headway. But despite the rapid progress, a series of fundamental questions have been raised, particularly about the size of the CMIM facility. Although CMIM funding was doubled to 240 billion, effective since May 2012, the swap amount has frequently been criticized as insufficient. Another fundamental issue that still needs to be agreed upon is the CMIM's role and how it fits in among existing regional and global financing facilities. AMRO's surveillance work is seen as vital to the overall success of the CMIM in regional financial cooperation. As other multilateral institutions involved in surveillance work have experienced, effective surveillance to support regional financial cooperation is a complicated task, strewn with obstacles. The primary task of this paper is to suggest possible areas in which the effectiveness of the CMIM and AMRO may be increased, despite constraints and limitations.
Keywords: E61; F15; F33; 330; cmim; amro; swap; surveillance; bilateral; multilateral; conditionalities; Internationales Währungssystem; Währungsunion; Wirtschaftsintegration; Finanzmarktregulierung; Ostasien